Cynanchum wilfordii Polysaccharides Suppress Dextran Sulfate Sodium-Induced Acute Colitis in Mice and the Production of Inflammatory Mediators from Macrophages. (20th June 2017) - Cho, Chang-Won; Ahn, Sungeun; Lim, Tae-Gyu; Hong, Hee-Do; Rhee, Young Kyoung; Yang, Deok-Chun; Jang, Mi
Abstract : We recently reported the immune-enhancing effects of a high-molecular-weight fraction (HMF) of CW in macrophages and immunosuppressed mice, and this effect was attributed to a crude polysaccharide. As polysaccharides may also have anti-inflammatory functions, we investigated the anti-inflammatory effects and related molecular mechanisms of a crude polysaccharide (HMFO) obtained from HMF of CW in mice with dextran sulfate sodium- (DSS-) induced colitis and in lipopolysaccharide-induced RAW 264.7 macrophages. HMFO ameliorated the pathological characteristics of colitis and significantly reduced production of proinflammatory cytokines in the serum. Histological analysis indicated that HMFO improved the signs of histological damage such as abnormal crypts, crypt loss, and inflammatory cell infiltration induced by DSS. In addition, HMFO inhibited iNOS and COX-2 protein expression, as well as phosphorylated NF- κ B p65 levels in the colon tissue of mice with DSS-induced colitis. In macrophages, HMFO inhibited several cytokines and enzymes involved in inflammation such as prostaglandin E2, nitric oxide, tumor necrosis factor- α, interleukin-6, inducible nitric oxide synthase, and cyclooxygenase-2 by attenuating nuclear factor- κ B (NF- κ B) and mitogen-activated protein kinases. HMFO attenuated inflammation both in vitro and in vivo, primarily by inhibiting NF- κ B activation. Our findings indicate that HMFO is a promising remedy for treating inflammatory bowel diseases, such as colitis.